PERLINDUNGAN HUKUM BAGI KONSUMEN AIR MINUM ATAS PELAYANAN PERUSAHAAN DAERAH AIR MINUM TIRTA INDRA KABUPATEN INDRAGIRI HULU - Meta Fitria; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
As a service provider company and providing non-profit public benefits,PDAMs should be oriented towards quality service quality, capable of providinghigh quality water that meets health requirements (colorless and odorless),continuity, innovative, so that PDAM Tirta Indra Kab Indragiri Hulu can defenditself, and in the future is expected to become a service company that can betrusted and proud by consumers, especially Indragiri Hulu Regency. However, inreality there are still many unattainable drinking water consumer rights, such asthe right to convenience, where consumers are less comfortable with the servicesof PDAMs, and the right to information, where PDAMs are not open toconsumers regarding quality information from the drinking water they consumeeach year.As for the purpose of writing this thesis is To know the implementation,constraints, and efforts in legal protection for consumers of drinking waterservices Tirta Indra Regional Water Company Indragiri Hulu regency.The conclusions can be obtained from this research is, First, theimplementation of legal protection for consumers of drinking water services TirtaIndra PDAM Indragiri Hulu regency is still not running properly. Second,constraints in the implementation of legal protection for consumers of drinkingwater services Tirta Indra PDAM Indragiri Hulu regency is the number ofcomplaints from consumers and the quality of drinking water. Third, the effortsmade by PDAM Tirta Indra Indragiri Hulu regency in overcoming the problemsof drinking water services to consumers, related to consumer complaints directlyhandled by Public Relations Section and Customers PDAM Tirta Indra, ondrinking water quality, PDAM Tirta Indra Indragiri Hulu do some fixes such asPlow Meter and Pam Browsing. The author's suggestion from this research is,First, PDAM Tirta Indra Kab. Inhu is expected to improve services in providingclean water and quality. Secondly, PDAM Tirta Indra Kab. Inhu is expected tominimize complaints from consumers to provide clean water services. Third,PDAM Tirta Indra Kab. Inhu is expected to continue working to overcomevarious problems related to his ministry.Keywords: Legal Protection - Consumer - PDAM